Perinephric toxic fat: impact on surgical complexity, perioperative outcome, and surgical approach in partial nephrectomy - Walach, Margarete; Schiefelbein, Frank; Schneller, Andreas; Schoen, Georg; von Klot, Christoph A.J.; Katzendorn, Olga; Mühlbauer, Julia; Nuhn, Philipp; Kriegmair, Maximilian; Harke, Nina Natascha (Urologia internationalis, 2023)
Introduction: To assess influencing factors on perinephric toxic fat (high Mayo Adhesive Probability [MAP] score) and the impact of high MAP scores on surgical complexity, perioperative outcome, and surgical approach in patients with localized renal tumors undergoing open (OPN) and robot-assisted partial nephrectomy (RAPN). Methods: 698 patients were included in this study. Based on preoperative imaging, adherent perinephric fat (APF) was assessed to define MAP scores. Regression analyses assessed influencing parameters for high MAP scores (≥3), predictors of surgical outcome, and influencing factors on surgical approach. Results: OPN was performed in 331 (47%) patients, and 367 (53%) patients underwent RAPN. Male gender (p < 0.001), age ≥65 (p < 0.001), and BMI ≥27.4 kg/m2 (p < 0.001) showed to be significantly influencing factors for the presence of APF. High MAP scores showed to be an influencing factor for a prolonged surgery duration (OR = 1.68, 95% CI 1.22-2.31, p = 0.002) and a significant predictor to rather undergo OPN than RAPN (OR = 1.5, 95% CI 1.05-2.15, p = 0.027). Conclusion: Older, male patients with high BMI scores have a higher risk for APF. The presence of APF increases surgery time and may have an impact on decision making regarding the preferred surgical approach.